Le peuplier, un arbre qui cache la forêt ? - Amélie Robert; Mouhamed Tebonou (Projets de Paysage)
This article examines the role of poplar groves in landscapes and considers their recent dynamics and related issues (including, at the local level, the UNESCO world heritage listing of the Loire Valley). Based on testimonials from different stakeholders and on aerial photographs analysed and compared in a GIS, the study is conducted on two sites in the region of Anjou. The first part of the article reveals the complexity of the discussions regarding poplar groves and examines the viewpoint of landscape conservationists. The second part considers the dynamics that have affected the poplar groves since the late 1980s. It shows that these plantations are the focus of tensions which extend beyond them. It also explains that it is the enclosure of the valley landscapes more than the development of these plantations that poses a problem which should be considered as related to agricultural decline. The factors of change are examined in the third part of the article. It emerges that although representations of the poplar groves may have guided public policy, regulations often carry little weight and that other factors must be considered to understand the decline which is under way.